ISLAMIC COUNSELING IN HANDLING DOMESTIC VIOLENCE CASES IN SLEMAN REGENCY - Reza Mina Pahlewi (JF Publisher, 2024)
Domestic violence is a violent act committed by one family member against another. It can be physical, emotional, sexual, or psychological. Domestic violence often occurs within the home and can include beating, verbal abuse, forced sexual intercourse, financial control, and intimidation. Domestic violence has a serious impact on the physical and mental welfare of the victim and can affect the whole family, including children. Preventing and handling domestic violence includes legal support, social services, and community education on the importance of healthy and respectful relationships. Domestic violence is a serious problem affecting many families in Indonesia, including in Sleman. This research aims to evaluate the effectiveness of Islamic counseling approach in handling domestic violence cases in Sleman. The research method used was a qualitative approach with in-depth interviews with 15 participants who participated in the Islamic counseling program, and counseling session participant observation. The results showed that the Islamic counseling approach significantly assisted victims of domestic violence to understand their roles and responsibilities in the family, reduce conflict, and improve their relationship with their partner. In addition, it also provided spiritual support that strengthened participants’ mental and emotional resilience. The research concludes that Islamic counseling is effective in overcoming domestic violence and suggests a wider application of this approach and the necessity for further research to explore the factors that affect the success of counseling.